Ileocolic Intussusception Due to Appendiceal Mucocele in Adult Patient - Mantas Balcytis; Vita Klimasauskiene; Kazimieras Brazauskas; Joseph W. Nunoo-Mensah (World Journal of Colorectal Surgery)
This article presents a case of a 32-year-old male who was admitted to the Department of General Surgery at Republican Vilnius University Hospital. Abdominal and pelvic computed tomography (CT) revealed a well-encapsulated, approximately 45-mm cystic mass near the cecum with signs of intussusception. During open surgery, an intussusception caused by an appendiceal mucocele was identified, and an ileocecal resection was performed. Postoperative pathological examination confirmed ileocecal intussusception and appendiceal mucocele. The patient recovered satisfactorily. This case underscores the rarity of appendiceal mucocele and the associated diagnostic challenges.